Stress, buckling and vibration analysis of bicycle wheels by finite element method - Foo Zhong, Yao Zhang (Nanyang Technological University, 2023)
Bicycles have been around for more than 200 years, and the design of bicycle wheel has changed much over the years. This final year project deals with the stress, buckling and free vibration analysis of spoked-wheel design that is commonly used nowadays. The effect of initial tension on the stress distribution and natural frequency is also studied. The student version of ANSYS Mechanical APDL software is used for the finite element analysis presented in this report. From the static analysis, it is found that in a pre-tensioned wheel, some of the spokes at the bottom of the wheel have decreased tension when the payload is applied whereas the other spokes have slightly increased tension. Also, when braking force and payload are applied on the wheel together, the tension on the spokes increases in the rear half of the wheel whereas the tension on the spokes decreases in the other half. Modal (Free Vibration) analysis has also been carried out. The effect of increasing initial tension on the natural frequencies has been studied. As the initial tension increases, two of the natural frequencies tend to decrease while the others remain relatively unaffected. Also, buckling analysis has been carried out to determine the critical value of spoke tension. At the critical value of spoke tension, the wheel tends to buckle as the rim gets pulled inwards due to the spoke tension.